Correlation of Job Satisfaction, Organizational Culture on Individual Behavior Through Motivation - Qoriani, Hersa Farida; Musfiroh, Luluk (SAFE-Network, 2023)
Organizational culture is a strategy to revive an organization that has sunk for a long time. a strong and resilient organization has an influence on individual employee behavior, meaning that the more employees are given information and given values about organizational culture in the company, the stronger the employee's commitment to the company. Research with a quantitative approach. The population in this study were all employees of PT. Kuda Laut Mas, Sidoarjo, namely 23 employees. The sampling used is saturation sampling technique. Based on the analysis of the results of the research and discussion that has been described previously, it can be concluded in this study Organizational culture has no significant effect on the motivation of employees of PT. Kuda Laut Mas Sidoarjo. Job satisfaction has a significant positive effect on employee motivation at PT. Kuda Laut Mas Sidoarjo. Organizational culture has a significant positive effect on the behavior of individual employees of PT. Kuda Laut Mas Sidoarjo. Job satisfaction has no significant on the behavior of individual employees of PT. Kuda Laut Mas Sidoarjo. Motivation has no significant on the behavior of individual employees of PT. Kuda Laut Mas Sidoarjo.